Brexit and corporate citizenship - Armour, J; Fleischer, H; Knapp, V; Winner, M (Springer, 2017)
The UK’s recent vote for Brexit has sparked a fierce debate over the implications for the rights of EU citizens living in the UK and UK citizens living in the rest of the EU. So far, however, there has been relatively little discussion of the implications of Brexit for legal persons—that is, corporate citizens of the EU, which may also be profoundly affected by consequent changes. The ECJ’s 1999 decision in Centros made clear that the freedom of establishment protects the entitlement of corporate persons formed in one EU Member State to carry on their business in another Member State. Since then, many entrepreneurs in continental European countries have chosen to form companies in the UK, while still carrying on their business in their home country. What will the consequences of Brexit be for such companies?